Análisis financiero de la lubricadora Servicentro 19 de la ciudad de Machala de los peridos 2011 – 2012 - Rueda Rodríguez, Faviola De Jesús (2014)
The thesis called Financial Analysis in Business "Servicentro 19" of the city of Machala during the period 2011-2012, was conducted as prescribed in the Regulation of Academic Regime Mode Distance Learning National University of Loja before opting Engineering Degree in Accounting and Auditing, CPA., and contribute substantially to the financial progress of the company. The objectives set at the beginning of this financial analysis are achieved with the application of different indicators. It began with the physical observation of the institution (administrative and financial), data collection was conducted through interviews implementing financial staff of the company as the manager, accountant and portfolio department. These interviews allowed the current situation of the company, and to establish the importance of financial analysis. In the final part we applied financial ratios for the local financial structure allowing to identify the profitability in terms of liquidity, skills and ways of compliance to meet its obligations in a short time, the effectiveness (efficiency and effectiveness) administrative, financial, tax and accounting with respect to the proper use for the resources of the company and obtain the best results; Important to know the level of debt that the company has today. With the application of financial analysis in Servicentro 19, has earned the Financial Report, which serve as an instrument of economic information to its owner and manager, so it is recommended to apply the suggestions here given, they will serve to strengthen company.